2022
DOI: 10.3390/healthcare10020247
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Dimension of Pandemic Fear and the Dual-Factor Model of Mental Health: The Role of Coping Strategies

Abstract: (1) Background: Current COVID-19 research has mainly focused on negative outcomes associated with fear of the pandemic with the examination of potentially positive outcomes remaining underexplored. Based on the dual-factor model of mental health, which postulates positive and negative dimensions, we assessed the influence of COVID-19 fear on both negative and positive mental health outcomes and examined the mediational role of coping strategies. (2) Methods: A convenience sample of 231 respondents participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(65 reference statements)
2
5
0
Order By: Relevance
“…The present study found a positive association between fear of COVID-19 and PTG, which is consistent with the findings of period studies on PTG (Fino et al, 2022a, 2022b). Most critically, this study showed a positive U-curve relationship between PTG and experiencing distress, that is, high levels of fear of COVID-19 are most associated with the greatest levels of growth.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found a positive association between fear of COVID-19 and PTG, which is consistent with the findings of period studies on PTG (Fino et al, 2022a, 2022b). Most critically, this study showed a positive U-curve relationship between PTG and experiencing distress, that is, high levels of fear of COVID-19 are most associated with the greatest levels of growth.…”
Section: Discussionsupporting
confidence: 92%
“…In line with existing research in general populations, our results show that large proportions (49.6%) experienced low mental well-being [ 31 ], and that these potential impacts were associated with age [ 32 ]. In contrast with a study in Romania, where those who were most likely to have anxiety were between 18–24 and 55–65 [ 32 ], in our sample low mental well-being was less common in older age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Considering age and sex/gender, no significant differences in relation to PTG were reported in some studies investigating these variables [37,40,46,49,50,59,62,63]. In contrast, in the study by Celdrán et al [38] and Fino et al [42], women reported higher levels of growth, but of all the sociodemographic variables considered in the study by Celdrán et al [38], only younger age significantly correlated with higher PTG, and the same was found in the study by Northfield and Johnston [55]; by contrast, in the study by Na et al [54], being female was associated with pandemic growth. In the study by Ikizer et al [46], only the level of education was a predictor of PTG, as higher levels of education were associated with lower levels of PTG, while being younger was only associated with negative outputs, such as higher levels of pandemic-related stress.…”
Section: Association Between Ptg and Sociodemographic Factorsmentioning
confidence: 88%